From spatial intervention to healthy ageing: proposing a Spatial–Social–Ecological framework for active ageing community renewal - Min Zhou; Yang Li; Jing Huang; Simeng Liu (Frontiers in Public Health, 2026)
Introduction Community renewal oriented toward active ageing has become an important strategy for addressing population ageing and urban regeneration. However, existing research often examines spatial, social and ecological factors separately, resulting in a limited understanding of how community renewal can promote sustainable health outcomes. Method This bibliometric analysis followed PRISMA 2020-guided procedures for literature identification and screening and analyzed 1,386 publications (716 international and 670 Chinese) published between 2015 and 2025, retrieved from the Web of Science Core Collection (SSCI, SCIE, A&HCI) and the China National Knowledge Infrastructure (CNKI). Results (1) The focus of research has clearly shifted from facility-oriented interventions to integrated approaches that encompass spatial, social and ecological aspects. (2) A conceptual Spatial–Social–Ecological (SSE) framework is proposed to organize the hypothesized relationships among environmental interventions, social participation, ecological healing, and healthy ageing. Discussion The proposed framework provides an evidence-informed theoretical perspective for understanding how community renewal may support healthy ageing and offers a conceptual basis for future empirical research and evidence-based community renewal policies.